Cultural Influence on Clinical Features of Depression - Gani, Rina Krismiati; Mahajudin, Marlina Setiawati; Budi Kristianto (Faculty of Medicine, Universitas Airlangga, 2022)
Introduction: Depression is a common cause of poor health throughout the world. Genotype factors and cultural environment will interact to influence the psychodynamics of a person's behavior in expressing depression. Objective: This paper aims to describe the influence of cultural factors on a person's psychodynamics and clinical features of depression. Methods: PubMed and Google Scholar were searched using the following keyword (depression) AND (clinical features OR clinical appearance) AND (psychodynamic) AND (cultural influences) using the journal publication filter for the 2014-2020 issues. We also used textbooks published in the last 10 years and were related to writing themes. Results: Every individual has